English-medium instruction in higher education in the Middle East and North Africa : policy, research and pedagogy - Scatolini, Sergio Saleem; Alhassan, Awad; Ali, Holi Ibrahim Holi; Curle, Samantha (London [England] : Bloomsbury Academic, 2022)
"English-Medium Instruction (EMI) is a rapidly growing global phenomenon in countries where English is a second or foreign language. This book focuses on empirical research studies conducted on this growing trend in the Middle East and North Africa, an under-researched area with regards to the effects and challenges of the implementation of EMI in higher education. The contributors are researchers with first-hand experience in countries in the region, including Iran, Kuwait, Morocco, Oman, Saudi Arabia, Sudan, and Turkey. Each chapter follows a consistent structure, allowing comparisons to be drawn between policies and practices in different countries. Topics covered include investigating perceptions and attitudes of both students and lecturers, opportunities and challenges afforded by EMI, as well as the evolution of EMI practices. By exploring these issues, through the lens of a decolonial critical approach, this volume informs theory underlying research into the phenomenon of EMI in the region."--
1. Introduction / Samantha Curle (University of Bath, UK) -- 2. English Medium of Instruction in the Arab World: A Decolonial Interrogation / Berrington Ntombela (University of Zululand, South Africa) -- 3. English Medium of Instruction Courses in Iran: University Students and Instructors' Attitudes / Ali Derakhshan (Golestan University, Iran), Mahboubeh Rakhshandehroo (Kyoto University of Foreign Studies, Japan) and Samantha Curle (University of Bath, UK) -- 4. The Role of English Medium of Instruction in the Internationalization of Omani Higher Education Institutions: Gains and Challenges / Holi Ibrahim Holi Ali, Sergio Saleem Scatolini and Qasim Salim Al Washahi (Rustaq College of Education, Oman) -- 5. Kuwaiti Students' Perceptions and Attitudes towards English-Medium of Instruction / Inas Y. Mahfouz (American University of Kuwait, Kuwait) -- 6. English Medium Instruction in Saudi Higher Education: Challenges and Prospects / Abdulwahid Al Zumor and Habib Abdesslem (King Khalid University, Saudi Arabia) -- 7. English Medium Instruction Programmes in Turkey: Evidence of Exponential Growth / Do gan Yuksel and Mehmet Altay (Kocaeli University, Turkey) and Samantha Curle (University of Bath, UK) -- 8. Languages of Instruction in North Africa: Attitudes and Policies Concerning English-Medium Instruction / Salah Troudi (University of Exeter, UK) -- 9. English as a Medium of Instruction in Morocco: Attitudes, Merits, Challenges, Strategies, and Implementation / Hassan Belhiah (Mohammed V University, Morocco) -- 10. English as a Medium of Instruction in Sudanese Higher Education Institutions: Opportunities and Challenges / Awad Alhassan (Dhofar University, Oman) -- References -- Index.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: English-medium instruction -- Middle East; English-medium instruction -- Africa, North; English language -- Study and teaching (Higher) -- Foreign speakers; Education and globalization; Electronic books